Providing a High Level of Safety Culture when Exporting Nuclear Power Technologies - Rudenko, V. A.; Popova, T. S.; Evdoshkina, Yu. A. (Глобальная ядерная безопасность, 2022)
The paper considers the concept and fundamental principles of safety culture which along with the high professionalism of service personnel in Russia and abroad as well as the reliable operation of all production and technical systems, are necessary conditions for nuclear and radiation safety of energy enterprises. Taking into account the influence of national culture on safety culture, training in the effective use of tools for preventing personnel errors along with the high quality of education of foreign students will contribute to the formation of a principled position in the field of safety and efficiency of functioning of nuclear facilities.